Identification of Extracellular Domain Residues Required for Epithelial Na(+) Channel Activation by Acidic pH - Collier, Daniel M. (American Society for Biochemistry and Molecular Biology, 2012)
A growing body of evidence suggests that the extracellular domain of the epithelial Na(+) channel (ENaC) functions as a sensor that fine tunes channel activity in response to changes in the extracellular environment. We previously found that acidic pH increases the activity of human ENaC, which results from a decrease in Na(+) self-inhibition. In the current work, we identified extracellular domain residues responsible for this regulation. We found that rat ENaC is less sensitive to pH than human ENaC, an effect mediated in part by the γ subunit. We identified a group of seven residues in the extracellular domain of γENaC (Asp-164, Gln-165, Asp-166, Glu-292, Asp-335, His-439, and Glu-455) that, when individually mutated to Ala, decreased proton activation of ENaC. γ(E455) is conserved in βENaC (Glu-446); mutation of this residue to neutral amino acids (Ala, Cys) reduced ENaC stimulation by acidic pH, whereas reintroduction of a negative charge (by MTSES modification of Cys) restored pH regulation. Combination of the seven γENaC mutations with β(E446A) generated a channel that was not activated by acidic pH, but inhibition by alkaline pH was intact. Moreover, these mutations reduced the effect of pH on Na(+) self-inhibition. Together, the data identify eight extracellular domain residues in human β- and γENaC that are required for regulation by acidic pH.